PENGARUH VARIASI BASIS TERHADAP DAYA SIMPAN SALEP YANG MENGANDUNG EKSTRAK ETANOL DAUN BELIMBING WULUH (Averhoa bilimbi (L)) - Lestari, Tri Puji; Kurniawati, Evi; Widyaningrum, Esti Ambar (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Starfruit wuluh, scientifically known as Averrhoa blimbi L., contains secondary metabolites such as flavonoids and tannins, which function as antibacterial agents. The extract of starfruit wuluh leaves is formulated into a ointment for easy application. The selection of a suitable ointment base is crucial to achieve the formulation's effectiveness. Understanding the influence of using different bases, specifically oil-in-water emulsion base and water-soluble ointment base, on the stability of ointment containing ethanol extract of starfruit wuluh leaves is the aim of this research. Stability testing is conducted for two weeks at room temperature. Physicochemical tests include organoleptic evaluation, homogeneity, adhesiveness, pH, and spreading ability of the formulation. The results indicate that the variation in the type of base does not affect organoleptic aspects, homogeneity, and pH during storage but does impact adhesiveness and spreading ability of the ointment containing starfruit wuluh leaf extract during storage